ESCRT and autophagies: Endosomal functions and beyond. (February 2018) - Lefebvre, Christophe; Legouis, Renaud; Culetto, Emmanuel
Graphical abstract: Highlights: ESCRT complexes participate to microautophagy and macroautophagy processes. ESCRT are required for endosomal membrane deformation to internalize cytosolic components in endosomal microautophagy. Maturation of endosome by ESCRT machinery is required for fusion with autophagosome to form amphisome during macroautophagy. ESCRT subunits could be involved in final maturation step of autophagosome. Recent studies indicate novel cross-interactions between ESCRT and macroautophagy proteins. Abstract: ESCRT (endosomal sorting complex required for transport) machinery has been initially identified for its role during endocytosis, which allows membrane proteins and lipids to be degraded in the lysosome. ESCRT function is required to form intraluminal vesicles permitting internalization of cytosolic components or membrane embedded cargoes and promoting endosome maturation. ESCRT machinery also contributes to multiple key cell mechanisms in which it reshapes membranes. In addition, ESCRT actively participates in different types of autophagy processes for degrading cytosolic components, such as endosomal microautophagy and macroautophagy. During macroautophagy, ESCRT promotes formation of multivesicular bodies, which can fuse with autophagosomes to generate amphisomes. This latter fusion probably brings to autophagosomes key membrane molecules necessary for the subsequent fusion with lysosomes. Interestingly, during macroautophagy, ESCRT proteins could be involved in non-canonical functions such as vesicle tethering or phagophore membrane sealing. Additionally, ESCRT subunits could directly interact with key autophagy related proteins to build a closer connection between endocytosis and autophagy pathways.